Production and secretion of interferon-gamma (IFN-gamma) in children with atopic dermatitis. - Tang, M (1994)
IFN-gamma is known to be a major inhibitor of IgE synthesis in vitro. Recent studies demonstrating reduced production of IFN-gamma in children and adults with atopic dermatitis and elevated serum IgE suggest a similar role for this cytokine in vivo. The reasons for this reduced IFN-gamma production are not known. One possibility is that atopic individuals have a reduced population of cells producing IFN-gamma in vivo. Using a fluorescence-labelled antibody to detect intracellular IFN-gamma, the percentage of IFN-gamma-producing cells was determined in children with atopic dermatitis and in non-atopic controls. Children with atopic dermatitis had a greater percentage of IFN-gamma-producing cells in unstimulated cultures compared with controls, indicating in vivo activation of lymphocytes in the atopic group. This could reflect the significant degree of inflammation present in these children, or the presence of bacterial infection or colonization. Although secretion of IFN-gamma after stimulation with phorbol myristate acetate (PMA)/Ca was significantly lower in children with atopic dermatitis compared with controls, the percentage of IFN-gamma-producing cells in the stimulated cultures from this group was equivalent to controls. This demonstrates that the reduced ability of atopic children to secrete IFN-gamma in vitro does not relate to a lack of IFN-gamma-producing cells, but to a difference in the regulation of IFN-gamma production beyond the stage of signal transduction.